Families, fortunes, and footwear : reaching out to the fourth generation of Brazil's Lupo S.A. - Ward, John, (SAGE Knowledge. Cases., 2017)
A successful third-generation family business explores whether or not to continue in business as a family into the fourth generation. If they do decide to move forward as a family business, how can they cultivate knowledge and interest among the forty-plus fourth-generation family members?